Bioethanol production with different dosages of the commercial acrylamide polymer compared to a bioextract in clarifying sugarcane juice - de Freita, Cristhyane Millena [UNESP]; Freita, Lidyane A. [UNESP]; Tralli, Leticia F. [UNESP]; Silva, Aline F. [UNESP]; Mendes, Franciele Q. [UNESP]; Teixeira, Vitor [UNESP]; Mutton, Marcia J. R. [UNESP] (FapUNIFESP (SciELO), 2017)
One of the most important steps is to clarify the juice, which are added synthetic polymer acrylamide base, aiming the fast settling of impurities present in the juice. However, this input is expensive and may have carcinogenic and neurotoxic actions to humans. The search for new natural flocculants that have similarity with the commercial product is of great value. A bioextract that may be promising and has coagulant action is the Moringa oleifera Lam. In this context, the objective of the research was to evaluate the consequences of the use of moringa seed extracts and various concentrations of commercial polymer, such as sedimentation aids in clarifying sugarcane juice in the ethanol production, comparing the efficiency of the bioextract moringa. In the treatment of the juice, excessive addition of flocculants can result in reduction of sugars. The bioflocculant moringa was similar in technological features and the fermentative viability compared to usual dose of commercial polymer in Brazil. The fermentation efficiency was also higher for this flocculant, followed by moringa extract. The results obtained in this research indicate potential to the moringa bioextract, particularly in countries where the doses of flocculants are higher than 5 mg.L-1.
Keywords: Biofuels; Biopolymers; Juice treatment; Moringa oleifera Lam